(3cTa GdQjf aj CMhGd GdYjfs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg efhQG GdCHUGQ hHYO agPG JLQjO eG jLH MaXg Ydi GdeJSe HUfGYI GdcMd ef cJGHi GdehShe HcTa GdQjf ai CMhGd GdYjf s
(3BNQgG (B:s
(3GdYdg GdeYQhaI HGdJhGdjd gi Cf jaWQ ef GdYjf YfO Gdfhe hSY jSjQ hgPG JeGe eG CQOfG CKHGJg ai gPG GdJLQjO hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B200s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1490s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs